Our Polar Flight: The Amundsen-Ellsworth Polar Flight - Amundsen, Roald, 1872-1928; Ellsworth, Lincoln, 1880-1951; Larsen, Hjalmar Riiser-, 1890-1965; Dietrichson, Leif, 1890-1928; Ramm, Fredrik, 1892-1943; Bjerknes, J. (Jacob Aall Bonnevie), 1897-1975 (Dodd, Mead and Co., 1925)
New York: Dodd, Mead and Co., 1925